Socialization of Sports Massage for Visitors of Pakui Park in Makassar City - Zainuddin, M. Said; Usman, Arifuddin; Awaluddin; Badaru, Benny; Imran Hasanuddin, M. (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2024)
This study investigates the impact of sport massage socialization on the knowledge and interest of visitors to Pakui Park in engaging in physical activity. A total of 100 visitors, comprising 50 men and 50 women, participated in this study. The results reveal that sport massage socialization significantly enhances the knowledge and interest of visitors to Pakui Park in participating in physical activity. Furthermore, the socialization of sport massage improves visitors' understanding of the benefits of sport massage in preventing injuries and enhancing physical performance. The findings suggest that sport massage socialization is an effective strategy for promoting physical activity and a healthy lifestyle among visitors to Pakui Park. This study contributes to the existing body of knowledge on the role of sport massage in promoting physical activity and provides insights for policymakers, health professionals, and park administrators to develop targeted interventions aimed at encouraging visitors to engage in regular physical activity and adopt a healthy lifestyle.